High Dosage of Vitamin D Regulates the Energy Metabolism and Increases Insulin Sensitivity, but are Associated with High Levels of Kidney Damage - Gaspar, Rafael Calais; Botezelli, José Diego; Kuga, Gabriel Keine [UNESP]; Muñoz, Vitor Rosetto; Coope, Andressa; Pereira, Rodrigo Martins; da Silva, Adelino Sanchez Ramos; Cintra, Dennys Esper; de Moura, Leandro Pereira; Ropelle, Eduardo Rochete; Pauli, José Rodrigo (Wiley, 2017)
(Table presented.). Metabolic disorders are responsible for more than 60% of all deaths worldwide. Calcitriol or vitamin D (vitD) deficiency is associated with a large proportion of these diseases is an important therapeutic target for exploration. This study evaluated the administration of high doses of vitD (3000 IU/kg) in obese and insulin-resistant C57BL/6J mice. Our results demonstrated that although high doses of vitD provided metabolic benefits such as increased insulin sensitivity and decreased body mass, this was associated with significant damage in the kidneys of obese mice. These findings support the role of vitD as a therapeutic strategy against metabolic disorders. However, caution is required with the dose administrated, and the renal damage associated still needs to be investigated. Drug Dev Res 78 : 203–209, 2017. © 2017 Wiley Periodicals, Inc.
Keywords: insulin; obesity; vitamin D